Model Kesabaran Qur’ani: Studi Tematik Pada Ayat-Ayat Tentang Resiliensi Kesabaran - Hasfiana; Andi Miswar; Halimah Basri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
resilience through a thematic tafsir approach. The study aims to formulate a conceptual model of patience that goes beyond a purely normative ethical attitude and functions as an integrated mechanism of inner resilience shaping faith, psychological stability, and spiritual maturity. The primary data consist of selected Qur’anic verses, particularly QS. Al-Baqarah [2]:153 and 155, QS. Ar-Ra‘d [13]:22, QS. Al-A‘raf [7]:200, and QS. Al-Anfal [8]:46, which are analyzed through a synthetic reading of classical and contemporary Qur’anic exegesis. The findings indicate that Qur’anic patience operates in a layered and systemic manner, encompassing the strengthening of faith, Qur’an-based cognitive reframing of trials, spiritual tranquility through worship and isti‘ādhah, adaptive moral behavior, and self-transformation through life’s challenges. This model demonstrates that patience in the Qur’anic perspective is not a passive form of endurance, but an active spiritual force that enables individuals to remain resilient, adaptive, and growth-oriented amid adversity. Consequently, Qur’anic patience functions as a foundational framework of spiritual resilience that structures continuous faith development at both personal and social levels.